EMIC waves and associated relativistic electron precipitation on 25–26 January 2013. Issue 11 (25th November 2016) - Zhang, Jichun; Halford, Alexa J.; Saikin, Anthony A.; Huang, Chia‐Lin; Spence, Harlan E.; Larsen, Brian A.; Reeves, Geoffrey D.; Millan, Robyn M.; Smith, Charles W.; Torbert, Roy B.; Kurth, William S.; Kletzing, Craig A.; et al.
Abstract: Using measurements from the Van Allen Probes and the Balloon Array for RBSP Relativistic Electron Losses (BARREL), we perform a case study of electromagnetic ion cyclotron (EMIC) waves and associated relativistic electron precipitation (REP) observed on 25–26 January 2013. Among all the EMIC wave and REP events from the two missions, the pair of the events is the closest both in space and time. The Van Allen Probe‐B detected significant EMIC waves at L = 2.1–3.9 and magnetic local time (MLT) = 21.0–23.4 for 53.5 min from 2353:00 UT, 25 January 2013. Meanwhile, BARREL‐1T observed clear precipitation of relativistic electrons at L = 4.2–4.3 and MLT = 20.7–20.8 for 10.0 min from 2358 UT, 25 January 2013. Local plasma and field conditions for the excitation of the EMIC waves, wave properties, electron minimum resonant energy E min, and electron pitch angle diffusion coefficient Dαα of a sample EMIC wave packet are examined along with solar wind plasma and interplanetary magnetic field parameters, geomagnetic activity, and results from the spectral analysis of the BARREL balloon observations to investigate the two types of events. The events occurred in the early main phase of a moderate storm (min. Dst * = −51.0 nT). The EMIC wave event consists of two parts. Unlike the first part, the second part of the EMIC wave event was locally generated and still in its source region. It is found that the REP event is likely associated with the EMIC wave event. Key Points: RBSP‐B observed EMIC waves and BARREL‐1T detected REP close by on 25‐26 January 2013 The pair of the events is the closest both in space and time among all the events from the two missions The REP is likely associated with the EMIC wave activity